The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1365-201x.2004.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immersion water temperature on whole‐body fluid distribution in humans

Abstract: These observations have two implications. First, one cannot assume that PV changes reflect those of the entire extracellular compartment. Second, since immersion also increases interstitial fluid pressure, fluid leaving the interstitium must have been rapidly replaced by intracellular water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…Plasma oncotic pressure is decreased in HOWI resulting in hemodilution, whereas plasma osmolarity is unchanged. Amino acids and potassium are increased in the plasma suggesting that the majority of the fluid shifted is out of the intracellular compartment (83,201,358). In spite of this, interstitial fluid volume and lymph flow do not change in HOWI.…”
Section: Circulatory Responses and Fluid Shiftsmentioning
confidence: 87%
See 4 more Smart Citations
“…Plasma oncotic pressure is decreased in HOWI resulting in hemodilution, whereas plasma osmolarity is unchanged. Amino acids and potassium are increased in the plasma suggesting that the majority of the fluid shifted is out of the intracellular compartment (83,201,358). In spite of this, interstitial fluid volume and lymph flow do not change in HOWI.…”
Section: Circulatory Responses and Fluid Shiftsmentioning
confidence: 87%
“…Since ANP reduces transcapillary fluid exchange (201,202), it is possible that ANP contributed to the reduction in PV in cold water. This study indicated that changes in PV were not associated with changes in total extracellular fluid volume at least in immersion (358). A further study by Stocks et al (358) established that acclimation to 14 days of cold water immersion does not qualitatively or quantitatively alter the fluid shifts during 1 h HOWIs.…”
Section: Renal Responses To Intrathoracic Volume Expansionmentioning
confidence: 89%
See 3 more Smart Citations